Influência da salinidade no crescimento de Physalis peruviana L. - Coutinho, Mileide Santos (2017)
The cultivation of potential fruit species in the semiarid region, using a hydroponic system, arises in an attempt to diversify and boost the economy, especially small and medium producers in this region. However, studies are needed to evaluate the growth, productivity and adaptation of these species. The objective of this study was to evaluate the growth and nutritional profile of Physalis peruviana in a hydroponic floating system, considering different levels of salinity of the water artificially produced with NaCl. The experiment was carried out in a protected environment (greenhouse), where a randomized block design (RBD) was used, with four blocks, being tested five concentrations of salinity: 0; 20; 30; 40 and 60 mM NaCl. At each interval of 10 days, the following measurements were obtained: stem and root lengths, total leaf area and neck diameter and dry matter masses of plants. After 48 days of treatment, in addition to the growth analyzes, the nutrient contents of the leaves were quantified. Data were submitted to analysis of variance and analyzed by means test and regression curves. Leaf nutrient contents were only descriptive. Within the expected, the salinity of the medium restricted the growth of plants of fisális. The variables total dry mass (TDM), absolute growth rate (AGR) and number of leaves (NL) were those that suffered the greatest reductions with the increase of the salinity of the medium. In relation to the leaf nutrient profile, it was observed that the higher the Na + and Cl- concentration in the leaves, the lower the K +, Ca2 + and Mg2+ concentrations. According to the data of total dry mass, it was possible to determine the P. peruviana salinity tolerance index (STI), which presented mean values> 70% in most of the experimental period at concentrations of 20 and 30 mM, demonstrating that P. peruviana species is moderately tolerant to salinity. In addition, it was considered in this work that high NaCl levels led to a nutritional imbalance, where sodium ion was the main cause of interferences during growth.